La notion de génération et les rapports de domination dans l’écriture d’une histoire de l’art au Yémen - Anahi Alviso-Marino (Revue des Mondes Musulmans et de la Méditerranée)
The notion of jîl (generation) as it emerges in published and unpublished texts of Yemeni visual artists offers a unique opportunity to question how art history is built in Yemen. By studying how artists illustrate, document, and inform a partially written art history in these documents, this article analyzes this material, linking the process of individual objectification with the hierarchies and relations of domination that structure the socio-professional networks of artists. The first half of this article is dedicated to explaining a certain number of methodological questions that underlie the research and writing of art history in Yemen. The second part focuses on a collection of writings analyzing the notion of generation by studying and questioning the ways in which relations of domination are embedded into these sources. This approach aims to illustrate how the hierarchies that texts attempt to establish are observed in practice and how artists subsequently perform and reproduce them.